Evaluación de la eficiencia de inhibidores de corrosión base agua para aguas de formación en la empresa Chemdrill S.A.S. (2018)
The phenomenon of corrosion is a problem that affects several industrial sectors, among these is the oil sector; directly affecting the structures of coating, production and drilling. One of the solutions implemented in the oil industry is the use of water-based corrosion inhibitors. These inhibitors have several advantages, since their application must be diluted when working in ppm concentrations, postponing corrosion by altering the surface of the metal, increasing the useful life of equipment, it is not necessary to remove it before carrying out an operation, Films generated are thin and transparent, reduce costs in terms of product quantities, mitigate environmental damage due to its low toxicity, prolonged protection time, do not work by removing air and water. Currently, the company implements a method of selecting water-based corrosion inhibitors in the field by speed of material wear, which consists of the installation of laminar coupons in the flow line at intermediate and final points of the sections to be protected, taking into account counts the weight of the coupon before and after being exposed to the medium; this methodology represents costs of $ 8'128,612. For this reason, the present work has the purpose of generating a proposal for the evaluation of the efficiency of water-based corrosion inhibitors for the company Chemdrill S.A.S. at the laboratory level that reduces costs in its implementation.